Research in sport climbing - Künzell, S.; Balas, J.; España-Romero, V.; Giles, D.; Legreneur, P. (Frontiers in Psychology, 2021)
Sport climbing is enjoying growing popularity—on rock in the great outdoors and especially indoors on artificial climbing walls in inner-city gyms. Increased enthusiasm and participation in the sport has led also to greater interest in competitive climbing—ultimately leading to sport climbing being included as an Olympic discipline in Tokyo 2020 and beyond. It is hoped that the sport being showcased on the international stage will result in increased participation around the world. Along with participation in climbing, interest in and research on the science of the sport has increased considerably. In 2011, the International Rock Climbing Research Association (IRCRA) was founded, which holds an international congress on research in climbing every 2 years. This Research Topic is the outgrowth of the last meeting of IRCRA in Chamonix in the summer of 2018, organized by its current president Pierre Legreneur. Two strands with different objectives are emerging in climbing research. The first strand focuses on understanding and improving climbing performance. Performance-determining factors are sought and found, and a wide variety of training procedures are examined for their effectiveness. Conversely, the second strand focuses on climbers as a special population to be studied in terms of their perceptions, stress processing, and other personality traits. Such characteristics are examined to determine whether the practice of climbing promotes outcomes that are educationally or therapeutically desirable or just scientifically interesting. This Research Topic is predominately focused on the first strand.